Hemocompatibility of Superhemophobic Titania Surfaces. Issue 4 (21st December 2016) - Movafaghi, Sanli; Leszczak, Victoria; Wang, Wei; Sorkin, Jonathan A.; Dasi, Lakshmi P.; Popat, Ketul C.; Kota, Arun K.
Abstract : The hemocompatibility of superhemophobic surfaces is investigated and compared with that of hemophobic surfaces and hemophilic surfaces. This analysis indicates that only those superhemophobic surfaces with a robust Cassie–Baxter state display significantly lower platelet adhesion and activation. It is envisioned that the understanding gained through this work will lead to the fabrication of improved hemocompatible, superhemophobic medical implants.